Letter (copy) : Ray Cox Memorial - Citrine, Walter, 1887-1983
042-0069-001 WMC/WJB/MS/307 International 7th February, 1938. Mr. L. Witt, "Upwey", Hatley Road, Bitterne, Southampton. Dear Mr. Witt, RAY COX MEMORIAL. Supplementing our letter to you of the 1st instant, we enclose for your information, a letter which we have received from Mr. G. Stolz, Assistant Secretary of the International Federation of Trade Unions (Mr. Schevenels, the General Secretary) being away attending a meeting in Geneva). Yours faithfully, General Secretary. 292/946/42/69